Safety of an extension of use of Yarrowia lipolytica yeast biomass as a novel food pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA); Dominique Turck; Torsten Bohn; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; Alexandre Maciuk; Inge Mangelsdorf; Harry J. McArdle; Androniki Naska; Kristina Pentieva; Alfonso Siani; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the safety of an extension of use of Yarrowia (Y.) lipolytica yeast biomass as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The extension of use pertains to the use of the NF as a food ingredient in a number of food categories, in foods for special medical purposes and in foods for total diet replacement for weight control. In 2018, Y. lipolytica was attributed the qualified presumption of safety (QPS) status for production purposes, including food and feed products based on biomass. The Panel considers that the data provided sufficient information with respect to the stability of the NF, also when used as a food ingredient. The concentrations of the analysed processing contaminants do not raise safety concerns. The Panel also considers that consumption of the NF is not nutritionally disadvantageous under the proposed conditions of use. The Panel concludes that the NF, Y. lipolytica yeast biomass, is safe under the proposed conditions of use.